2019
DOI: 10.1177/0091647119842409
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Humility of Religious Communities and Well-Being in Sexual Minority Persons

Abstract: Cultural humility has been shown to enhance cross-cultural relationships, but little research has explored how individuals perceive the cultural humility of a salient group. In the current study, we examined how perceptions of the cultural humility of a religious community affect the well-being of sexual minorities, who frequently experience discrimination, minority stress, and relational conflict in faith communities. As predicted, results indicated higher levels of perceived cultural humility in religious co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In this way, cultural humility can enhance cross-cultural interactions and relationships (Hook et al, 2017). For example, cultural humility in Christians has been associated with hospitality toward Syrian refuges (Captari et al, 2019) and psychological well-being and belongingness of sexual minority individuals (Mosher et al, 2019). Such outcomes can offer spiritual and relational benefits to Christian communities even when they may disagree on religious and ideological convictions.…”
Section: A Christian Rationale For Multiculturalism Social Justice mentioning
confidence: 99%
“…In this way, cultural humility can enhance cross-cultural interactions and relationships (Hook et al, 2017). For example, cultural humility in Christians has been associated with hospitality toward Syrian refuges (Captari et al, 2019) and psychological well-being and belongingness of sexual minority individuals (Mosher et al, 2019). Such outcomes can offer spiritual and relational benefits to Christian communities even when they may disagree on religious and ideological convictions.…”
Section: A Christian Rationale For Multiculturalism Social Justice mentioning
confidence: 99%
“…Furthermore, collecting data from paired clients and therapists and using dyadic data analysis strategies could shed light on interactions between client and therapist CH over time. Exploring client perceptions of overall clinic (i.e., not only therapist) CH would also be helpful, as a study on sexual minorities' perceptions of religious community CH (Mosher et al, 2019) illuminated the potential effects of a salient group virtue on individual outcomes. This study's practice‐based design examined change in clients during psychotherapy but did not track specific interventions that might have influenced outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, collecting data from paired clients and therapists and using dyadic data analysis strategies could shed light on interactions between client and therapist CH over time. Exploring client perceptions of overall clinic (i.e., not only therapist) CH would also be helpful, as a study on sexual minorities' perceptions of religious community CH (Mosher et al, 2019) (Captari et al, 2019;Hartman et al, 2022), whereas individual-level interventions can focus on challenging preconceived notions and falsehoods about the other and identifying points of shared humanity, that is, "possible bridges" between self and other (Hartman et al, 2022;Rober & De Haene, 2014, p. 18). Examination of the effectiveness of CH interventions to bridge differences and improve relational dynamics is greatly needed.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…This is in comparison to SM people who are associated with more affirming-inclusive religions (Lease et al, 2005; Levy & Reeves, 2011; Yakushko, 2005), where the religious messages support and encourage sexuality in numerous forms and one can be both religious and an SM individual. For example, Mosher et al (2019) found cultural humility within a religious organization is associated with less depression, less anxiety, and more sense of belonging for SM congregants. In this work, Mosher et al (2019) define cultural humility as both an intrapersonal and interpersonal phenomenon marked by critical reflection on one’s own limitations and being open to understanding other cultural worldviews.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mosher et al (2019) found cultural humility within a religious organization is associated with less depression, less anxiety, and more sense of belonging for SM congregants. In this work, Mosher et al (2019) define cultural humility as both an intrapersonal and interpersonal phenomenon marked by critical reflection on one’s own limitations and being open to understanding other cultural worldviews. Affirming-inclusive religions place less emphasis on punitive religious constructs, in support of the current findings (Scheitle et al, 2010).…”
Section: Discussionmentioning
confidence: 99%